Alcohol use trajectories of adult Latinx immigrants during their first decade in the United States. (July 2020) - De La Rosa, Mario; Sanchez, Mariana; Wang, Weize; Angel Cano, Miguel; Rojas, Patria
Highlights: Findings revealed overall declines in pre- to post-immigration alcohol use. Gender, income, and national origin were associated with distinct drinking patterns. Results inform future alcohol intervention research on Latinx immigrants early in the immigration process. Abstract: Background: Despite important research advances on the alcohol use behaviors of Latinx immigrants, the bulk of existing evidence has focused on alcohol use patterns after immigrant's arrival to the US. The present study examines pre- to post immigration alcohol use trajectories among Latinx immigrants of diverse national origins throughout their first decade in the United States. Methods: Data for this longitudinal study was collected between 2007 and 2017. At baseline, retrospective pre-immigration alcohol use data was collected on 527 Cuban, South American and Central American participants ages 18–34 who immigrated to the US less than one year prior. Three subsequent follow-up assessments over the past 10 years have collected data on post-immigration alcohol use. Results: Overall decreases in pre- to post-immigration alcohol use were found. Gender, income, and national origin were associated with distinct drinking patterns after immigration. Conclusion: Findings underscore the importance of examining pre-immigration experiences among Latinx immigrants, in addition to longitudinal alcohol use patterns after immigration. This knowledge is important not only from an epidemiological perspective, but for the development of effective culturally relevant alcohol interventions targeting Latinx immigrants early in the immigration process.